Spatial gene expression profile of Wnt-signaling components in the murine enteric nervous system - Scharr, Melanie; Hirt, Bernhard; Neckel, Peter H. (Frontiers in Immunology, 2024)
Introduction Wnt-signaling is a key regulator of stem cell homeostasis, extensively studied in the intestinal crypt and other metazoan tissues. Yet, there is hardly any data available on the presence of Wnt-signaling components in the adult enteric nervous system (ENS) in vivo. Methods Therefore, we employed RNAscope HiPlex-assay, a novel and more sensitive in situ hybridization technology. By amplifying target specific signals, this technique enables the detection of low abundance, tightly regulated RNA content as is the case for Wnt-signaling components. Additionally, we compared our data to previously published physiological single cell RNA and RiboTag-based RNA sequencing analyses of enteric gliosis using data-mining approaches. Results Our descriptive analysis shows that several components of the multidi-mensional regulatory network of the Wnt-signaling pathway are present in the murine ENS. The transport and secretion protein for Wnt-ligands Wntless as well as canonical (Wnt3a and Wnt2b) and non-canonical Wnt-ligands (Wnt5a, Wnt7a, Wnt8b and Wnt11) are detectable within submucosal and myenteric plexus. Further, corresponding Frizzled receptors (Fzd1, Fzd3, Fzd6, and Fzd7) and regulatory signaling mediators like R-Spondin/DKK ligands are present in the ENS of the small and large intestine. Further, data mining approaches revealed, that several Wnt-related molecules are expressed by enteric glial cell clusters and are dynamically regulated during the inflammatory manifestation of enteric gliosis. Discussion Our results suggest, that canonical and non-canonical Wnt-signaling has a much broader impact on the mature ENS and its cellular homeostasis in health and inflammation, than previously anticipated.